2018 IEEE 16th International Conference on Industrial Informatics (INDIN) 2018
DOI: 10.1109/indin.2018.8472080
|View full text |Cite
|
Sign up to set email alerts
|

MeDI: Measurement-based Device Identification Framework for Internet of Things

Abstract: IoT systems may provide information from different sensors that may reveal potentially confidential data, such as a person's presence or not. The primary question to address is how we can identify the sensors and other devices in a reliable way before receiving data from them and using or sharing it. In other words, we need to verify the identity of sensors and devices. A malicious device could claim that it is the legitimate sensor and trigger security problems. For instance, it might send false data about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…By collecting traffic traces over 3 weeks, the authors indicated that their classification method can not only distinguish IoT from non-IoT traffic, but also identify specific IoT devices with over 95% accuracy. Yousefnezhad et al [211] developed Measurement-based Device Identification (MeDI), a framework based on device behavior or device profile. It monitors the data packets coming from smart devices to protect the server from receiving and spreading false data.…”
Section: E Authenticationmentioning
confidence: 99%
“…By collecting traffic traces over 3 weeks, the authors indicated that their classification method can not only distinguish IoT from non-IoT traffic, but also identify specific IoT devices with over 95% accuracy. Yousefnezhad et al [211] developed Measurement-based Device Identification (MeDI), a framework based on device behavior or device profile. It monitors the data packets coming from smart devices to protect the server from receiving and spreading false data.…”
Section: E Authenticationmentioning
confidence: 99%
“…Therefore, we adopt the payload data for device identification alongside header information and generated statistical features. The idea of using payload data or sensor measurements for device identification is initially proposed by [ 8 ]. This identification framework employs only payload data and some extracted statistical features from a public dataset without taking into consideration any attack scenarios.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For proof-of-concept, we implement a demonstrator system for the IoT system comprising of temperature and humidity sensors integrated through open standards called Open Messaging Interface (O-MI) and Open Data Format (O-DF). The present paper is an extended version of our paper, presented at the INDIN conference [ 8 ]. This paper significantly expands the feature sets and develops realistic results by running a real use-case, collecting real data, and evaluating the system through various attack scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…After identifying the type of the device, the system evaluates the vulnerability of the device, and isolates the device from the network if there is a security threat. In order to prevent illegal devices from stealing legal identity to attack the network and other devices, Yousefnezhad, Narges et al [26] proposed a device identification framework (MeDI) based on device behavior analysis. It identifies the security of the device by monitoring the data packet sent by the device and protect the server from accepting and spreading false data.…”
Section: Introductionmentioning
confidence: 99%